2009
DOI: 10.1111/j.1468-3083.2009.03211.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained improvement in joint pain and nail symptoms with etanercept therapy in patients with moderate‐to‐severe psoriasis

Abstract: In this study of moderate-to-severe plaque psoriasis, joint and nail symptoms were prevalent and patients with these symptoms had significantly greater HR-QoL impairment at baseline than unaffected patients. Etanercept provided significant improvement in symptom severity and HR-QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
2
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 42 publications
(74 reference statements)
8
84
2
9
Order By: Relevance
“…In the same study,patients treated with cyclosporine showed a 37% mean improvement in the NAPSI score (21 (25). The efficacy of etanercept in nail psoriasis has also been supported by other studies (7,26,27).…”
Section: Case Reportsupporting
confidence: 63%
“…In the same study,patients treated with cyclosporine showed a 37% mean improvement in the NAPSI score (21 (25). The efficacy of etanercept in nail psoriasis has also been supported by other studies (7,26,27).…”
Section: Case Reportsupporting
confidence: 63%
“…Etanercept, a TNF inhibitor, has shown efficacy in nail psoriasis in an open-label, randomised trial (CRYSTEL) including 564 patients with moderate to severe psoriasis with nail involvement receiving etanercept for 54 weeks, either continuously or in a paused treat-to-response fashion [12]. Mean NAPSI scores decreased by 28.9% at 12 weeks (p < 0.001) and continued to decrease by 51% at 54 weeks [12].…”
Section: The Advent Of New Treatment Options With Biologic Therapymentioning
confidence: 99%
“…Nail disease is more common in patients with more severe disease – for example, up to 80% of patients with psoriatic arthritis (PsA) often have nail involvement as part of their condition and, as with psoriasis patients, many rarely receive treatment for nail disease [5,6]. A high association between PsA and nail psoriasis has been noted in several studies [6,7,8,9,10,11,12,13,14]. In fact, a large population-based cohort study of 1,633 psoriasis patients found that psoriasis subjects with nail dystrophy are almost three times more likely to develop PsA than subjects without nail dystrophy [11].…”
Section: Introduction: Difficulty In Treating Psoriasis With Nail Invmentioning
confidence: 99%
“…Kao i u prethodnim studijama [16,19,20], podaci DLQI-a u ovoj studiji pokazuju da ispitanici sa kožnim bolestima imaju najviše skorove na simptomima i osećanjima, što verovatno ukazuje da je doživljaj fizičkog tela centralno pitanje u njihovim životima. Što se tiče visokih skorova za rad ili školovanje iz DLQI-a u ovoj studiji, oni ukazuju da kožna oboljenja nisu samo bolesti koje mogu narušiti fizički izgled pacijenata, već da one umnogome mogu ograničiti njihove aktivnosti na poslu ili školi [1,21,22].…”
Section: Diskusijaunclassified